Investigating the impact of managers' coaching behavior on employees' learning and performance in Pars Khodro Company - Morteza Akbari Mehrabad (Utan Kayu Publishing, 2025)
Today, the discussion of the characteristics of proper management and its tremendous effects on the performance of employees in Pars Khodro Company can be clearly seen, and recently new styles of management have been proposed that can be very effective in implementing strategies and pursuing the goals of the organization; This research investigates how the coaching behavior of managers affects the learning and performance of employees in Pars Khodro Company.The nature of the present research is descriptive-survey based on the objective criteria in the group of applied researches, based on the criteria of the data collection method of a field research.The analysis of the survey responses collected from 384 managers, supervisors and employees of Pars Khodro Company has been tested with SPSS26 and Smart PLS3 software.The findings of the research show that continuous learning is positively related to the work performance of employees. Continuous learning is positively related to the contextual performance of employees. Managers' coaching behavior positively moderates the relationship of employees' task performance, so that When managers exhibit specific coaching behavior, this relationship becomes stronger. Managers' coaching behavior positively moderates the relationship of employees' contextual performance, so that when managers exhibit specific coaching behavior, this relationship It gets stronger. Coaching behavior based on facilitation has a positive relationship with both types of employee performance. Coaching style based on inspiration has a positive and significant relationship with the task performance of employees and contextual performance of employees. Facilitation-based coaching behavior motivates employees in achieving their task as well as building strong interpersonal relationships with coworkers since they receive similar behavior from their managers